Variabilitas KloroCHLOROPHYLL-A VARIABILITY IN RELATION TO LEMURU FISH (Sardinella lemuru) CATCHING SEASON IN THE BALI STRAITfil-a Kaitannya Dengan Musim Penangkapan Ikan Lemuru (Sardinella lemuru) di Selat Bali - Syamsudin, Fadli; Fadhilah, Rizal; Syamsuddin, Mega Laksmini (Universitas Mataram, 2025)
Lemuru fish (Sardinella lemuru) is one of the main commodities in the waters of the Bali Strait. As a dynamic water environment, oceanographic conditions in the Bali Strait affect the high and low production of lemuru fish. Upwelling influences the presence of lemuru fish at various times of the year, causing changes in chlorophyll-a concentration. This study aims to evaluate the association between chlorophyll-a levels and the lemuru fishing season in the Bali Strait. The data used are chlorophyll-a image data and lemuru fish catch data spanning nine years (2014–2022). Chlorophyll-a data were visualized both temporally and spatially. Meanwhile, the catch data was transformed into CPUE values. The season index is used to determine the lemuru fishing season. The northwest season has the highest average CPUE (5,219 - 6,244 kg/trip), whereas the southeast season has the lowest CPUE (2700 - 5,590 kg/trip). Chlorophyll-a concentrations are highest in the southeast through the second transition season (1 - 1.5 mg/m3), and lowest in the northwest season (0.2 - 0.3 mg/m). The histogram illustrates that the largest CPUE acquisition occurs when chlorophyll-a concentration is low (<0.2 mg/m3). According to the fishing season index (IMP) of Sardinella lemuru fish, the highest fishing season time is in December (158.49%) and the lowest is in May (49.39%). The fishing season occurs when chlorophyll-a concentrations are low.